2012
DOI: 10.7166/15-2-204
|View full text |Cite
|
Sign up to set email alerts
|

A Performance Management Model for Physical Asset Management

Abstract: There has been an emphasis shift from maintenance management towards asset management, where the focus is on reliable and operational equipment and on effective assets at optimum life-cycle costs. A challenge in the manufacturing industry is to develop an asset performance management model that is integrated with business processes and strategies. The authors developed the APM 2 model to satisfy that requirement. The model has a generic reference structure and is supported by operational protocols to assist in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
1
4
0
2
Order By: Relevance
“…The results obtained by applying PLS path modeling reveal that PAM core practices have a statistically significant direct impact on operational performance (β = 0.432 **, t = 5.58). This result confirms the studies aimed at providing empirical evidence for the operationalization of PAM [62,84] and evidence for the performance outcomes of PAM [4,9,30]. Accordingly, the results of our empirical study illustrate the relative importance and interaction of core PAM practices and operational performance.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The results obtained by applying PLS path modeling reveal that PAM core practices have a statistically significant direct impact on operational performance (β = 0.432 **, t = 5.58). This result confirms the studies aimed at providing empirical evidence for the operationalization of PAM [62,84] and evidence for the performance outcomes of PAM [4,9,30]. Accordingly, the results of our empirical study illustrate the relative importance and interaction of core PAM practices and operational performance.…”
Section: Discussionsupporting
confidence: 88%
“…In particular, operational performance refers to the organization's ability to reduce operating costs, meet order cycle time, improve raw material utilization efficiency and meet delivery capacity [29]. Although some of the literature refers to the link between various aspects of PAM and operational performance dimensions [9,30,31], the literature review revealed a lack of a holistic approach towards PAM and its link to operational performance. Accordingly, an empirical investigation of the relationship between PAM and operational performance is required.…”
Section: Background Literature and Hypothesis Developmentmentioning
confidence: 99%
“…The third-highest ranking belongs to practices, a finding which supports previous studies as well. They have found that maintenance practices can have a critical impact on useful lifecycle and overall asset performance (Jooste and Page, 2004). The fact that preventative maintenance is the most significant practice in asset management confirms the results found by Fouladgar et al .…”
Section: Discussionmentioning
confidence: 99%
“…Asset management involves systematic and coordinated actions and practices, through which an organization optimally and sustainably oversees its assets and asset systems (Alfatih et al , 2015). Previous studies have described the importance of maintenance management in contributing to sustainable high performance of assets (Jooste and Page, 2004). Some of the maintenance strategies briefly introduced in this paper are preventive maintenance, corrective maintenance and predictive maintenance (Chandima and Markeset, 2010): Preventive maintenance is a helpful tool used to overcome issues that occur due to wear to assets.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Asset management involves systematic and coordinated activities and practices through which an organisation ideally and sustainably oversees its assets and asset systems (Alfatih et al, 2015). Jooste and Page (2004) asserted that the implementation of maintenance management results in sustainable assets. Thus, to ensure assets' sustainability, AM should seek to move away from traditional maintenance practices (Amadi-Echendu, 2004).…”
Section: Factors Affecting Asset Management Performance Maintenance Practicementioning
confidence: 99%